Efeito residual de fontes de fósforo e adubação fosfatada no crescimento do milho. - - Cruz, Caio Vilela [UNESP] (2015)
In acid soils the use of alternative sources in phosphate fertilizer can influence the efficiency of subsequent fertilization with soluble phosphate. The objective of this study was to evaluate the response of corn to phosphorus fertilizer and phosphorus content available in an Oxisol that was under the residual effect of phosphorus you were in two conditions of acidity. Two experiments were conducted in a greenhouse of the Department of Soil and Environmental Resources of the Faculty of Agricultural Sciences at the State University of São Paulo - UNESP- Botucatu. The first experiment was conducted under the residual effect of liming and experiment II Original acidic conditions. A completely randomized design was adopted in a factorial 4 x 5, with four replications. Treatments consisted of a soil which was fertilized with triple superphosphate (STF), rock phosphate (FNR) and two waste from the phosphate fertilizer industry (FP1 and FP2) with five doses of triple superphosphate (0, 30, 60, 90, 120 mg dm-3 P) for each source previously used. In this experiment the higher the solubility of the P source applied to correct fertilization in three successive cuts of Urochloa, the greater the influence of fertilizer replacement P for corn. The FP2 source had higher residual effect than other sources where the SFT doses did not affect biomass production and accumulation of P in corn plants to this source, the conditions imposed in experiments. The FP2 and RF sources obtained the highest available P values extracted by resin and the Mehlich 1. Even and a significant interaction between...